Pengaruh Pemberian Chlorhexidine Mouthwash 0.12% Terhadap Pencegahan Pneumonia Post Operasi Pada Pasien Ortopedi - Hertuida Clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2020)
Background: Orthopedic patients undergoing surgery with general anesthesia often require intubation and ventilation in order to maintain adequate airway and maintain optimal respiratory function. Both of these procedures can increase the risk of Pneumonia or VAP (Ventilator Associated Pneumonia). Purpose: The purpose of this study was to identify the effect of the implementation of oral hygiene with chlorhexidine mouthwash 0.12% in pre surgery in preventing VAP cases. Methods: The research design used was a pre experiment with a purposive sampling technique. Evaluation of the signs of postoperative pneumonia was carried out 4 (four) days after surgery using a clinical indicator called the CPIS (Clinical Pulmonary Infection Score). Results: The results of this study indicate that the application of oral hygiene in pre surgery using chlorhexidine mouthwash 0.12% is effective in preventing postoperative pneumonia in all respondents. Conclusion: Postoperative pneumonia (VAP) can be prevented by performing oral hygiene using chlorhexidine mouthwash 0.12% in pre surgery.